The Internalization of Social Stigma and the Solidarity of Religious Elites in Sustaining the Existence of Madrasah Diniyah - Agus Dwi Santosa (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
Educational modernization has transformed societal orientations in selecting educational institutions for children, creating challenges for the sustainability of madrasah diniyah as non-formal Islamic educational institutions. Most previous studies have explained the existence of madrasah diniyah through institutional management, curriculum development, and character-building aspects. However, limited research has examined the sustainability of madrasah diniyah from a social control perspective that operates through community social constructions and the role of religious actors. This study aims to analyze the sustainability of Madrasah Diniyah Tarbiyatul Mubtadi-ien in Slumbung Village, Ngadiluwih District, Kediri Regency, through the mechanisms of social stigma internalization and religious elite solidarity. The study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation and were analyzed using the interactive model of Miles and Huberman. The findings reveal that the internalization of social stigma functions as a mechanism of social control that encourages families to continue enrolling their children in diniyah education because religious education is perceived as a moral standard and a marker of community religious identity. Furthermore, religious elite solidarity, manifested through the role of religious leaders, functions as a form of social capital that fosters collective awareness, mobilizes community participation, and strengthens the legitimacy of madrasah diniyah. These findings indicate that the sustainability of madrasah diniyah is determined not only by internal institutional factors but also by the operation of social control rooted in religious culture, expressed through social stigma and religious elite solidarity. This study contributes to the development of non-formal Islamic education research by offering a social control perspective as a framework for explaining the sustainability of religious educational institutions in the era of modernization.